مقاصد القرآن في تزكية الإنسان - عبد المجيد النجار (International Institute of Islamic Thought, 2019)
اتّجهت الجهود التي بُذلت في بيان تزكية الإنسان في أغلبها إلى تزكية الإنسان في بُعده الفردي، ولم يكن لتزكية الإنسان في بُعده الجماعي إلا الحظّ اليسير، كما اتّجه أغلبها في تزكية الفرد إلى بُعده الروحي تصفيةً بالفضائل والعبادات، وترويضاً للنفس على كبح الشهوات واكتساب الفضائل، وكلُّ ذلك كان في الغالب من أجل الخلاص الفردي في يوم الحساب، وكان عند البعض مقترناً بهجران مشاغل الدنيا، والقعود عن أيّ كسبٍ ماديٍّ فيها. ولا نرى أنَّ التزكية كما جاء التوجيه إليها في القرآن الكريم تقفُ عند هذا الحدِّ الذي انتهى إليه الأكثرون في هذا الشأن، وإنما هي تتجاوز البُعد الفردي في الإنسان إلى البُعد الجماعي فيه، وتتجاوز البُعد الروحي إلى الأبعاد الفكرية والعملية، وتتجاوز هدف الخلاص الفردي في يوم الحساب إلى التعمير في هذه الدنيا التي هي مزرعة الآخرة. وهذه الأبعاد هي التي حاول هذا البحث بيانها استكمالاً للمفهوم الشامل للتزكية كما جاء في القرآن الكريم وفي السنة الشريفة. Most efforts made in explaining the purification of Man tended to address purification of the individual dimension, not the society. It also tended mostly to purify the spiritual dimension through acquiring virtues and worship and self-restraint to curb whims and self-desires for the sake of individual salvation in the Day of Judgment. Some people would associate this trend with the abandonment of worldly issues and giving up any material gain. Purification as instructed in the Holy Quran does not stand at the above mentioned points. Purification transcends the individual dimension to the collective one, and the spiritual dimension to the intellectual and practical. It also transcends the purpose of individual salvation in the hereafter to build human civilization in this world; as this world is considered the farm to grow what would be the harvest in the Hereafter. This paper attempts to present this comprehensive concept of purification as explained in the Holy Quran and in the honorable Sunnah of the Prophet.